Abundance - Klein, Ezra, 1984-; Thompson, Derek, 1986- (New York ; Amsterdam ; Antwerp ; London ; Toronto ; Sydney ; Melbourne ; New Delhi : Avid Reader Press, 2025)
To trace the history of the twenty-first century so far is to trace a history of unaffordability and shortage. After years of refusing to build sufficient housing, America has a national housing crisis. After years of limiting immigration, we don’t have enough workers. Despite decades of being warned about the consequences of climate change, we haven’t built anything close to the clean-energy infrastructure we need. Ambitious public projects are finished late and over budget—if they are ever finished at all. The crisis that’s clicking into focus now has been building for decades—because we haven’t been building enough. Abundance explains that our problems today are not the results of yesteryear’s villains. Rather, one generation’s solutions have become the next generation’s problems. Rules and regulations designed to solve the problems of the 1970s often prevent urban-density and green-energy projects that would help solve the problems of the 2020s. Laws meant to ensure that government considers the consequences of its actions have made it too difficult for government to act consequentially. In the last few decades, our capacity to see problems has sharpened while our ability to solve them has diminished.Progress requires facing up to the institutions in life that are not working as they need to. It means, for liberals, recognizing when the government is failing. It means, for conservatives, recognizing when the government is needed. In a book exploring how we can move from a liberalism that not only protects and preserves but also builds, Klein and Thompson trace the political, economic, and cultural barriers to progress and propose a path toward a politics of abundance.
Kniha se zabývá zásadními problémy současné americké společnosti, které pramení z dlouhodobého nedostatečného budování – ať už jde o bydlení, infrastrukturu, pracovní sílu či energetiku. Autoři ukazují, jak regulační opatření a politická řešení minulých desetiletí postupně začala bránit rozvoji, urychlování veřejných projektů i schopnosti reagovat na klimatickou krizi. Publikace nabízí politicko-ekonomickou analýzu toho, jak se z dobrých úmyslů minulosti staly bariéry současnosti, a představuje vizi „politiky hojnosti“, která by dokázala překonat stagnaci, obnovit schopnost společnosti stavět a tvořit a otevřít prostor pro dlouhodobě udržitelný pokrok.
Obsahuje bibliografické odkazy a rejstřík
Keywords: 20.-21. století; hospodářská politika; hospodářská stagnace; udržitelný rozvoj; ekonomická transformace; politická transformace; sociální změna; Spojené státy americké; monografie; 20th-21st centuries; economic policy; economic stagnation; sustainable development; economic transformation; political transformation; social change; United States; monographs